2016
DOI: 10.1007/s11832-016-0770-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the mechanical strength of hip spica cast between a conventional and a new method of application

Abstract: PurposeThe current technique of hip spica application is mostly based on a publication by Kumar (J Pediatr Orthop 1(1):97–99, 1981). We modified the technique of hip spica application in order to reduce the rate of breakage across the hip joint and designed this study to compare the strength between hip spica applied according to Kumar’s technique and the new technique.MethodsWe created 12 hip spica casts with 24 hips according to Kumar’s technique, and another 12 casts according to a new technique. The two ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…171 The method is used, with some modifications, to the present day. 172 Regardless of the type of the tested tissue, the comparison of features of the tested ECM sample (tested sample) and native tissue (control sample) that has not been bioengineered may be tested with a mechanical testing machine (e.g., Instron) by using compression loading and/or stretching force to failure in flexion, extension, abduction and adduction. The amount of tested samples must be appropriate for further statistical analysis.…”
Section: Evaluation Of the Properties Characteristics And Standardimentioning
confidence: 99%
“…171 The method is used, with some modifications, to the present day. 172 Regardless of the type of the tested tissue, the comparison of features of the tested ECM sample (tested sample) and native tissue (control sample) that has not been bioengineered may be tested with a mechanical testing machine (e.g., Instron) by using compression loading and/or stretching force to failure in flexion, extension, abduction and adduction. The amount of tested samples must be appropriate for further statistical analysis.…”
Section: Evaluation Of the Properties Characteristics And Standardimentioning
confidence: 99%
“…Wan et al 110 performed a biomechanical analysis of the strength of Kumar’s standard spica application versus their proposed method incorporating strut wraps beneath the hips of the patient imparting increased stiffness and load-to-failure at the hip joint. This was a purely mechanical study and no patient outcomes or comparisons were reported.…”
Section: Techniquesmentioning
confidence: 99%